2011
DOI: 10.3389/fpsyg.2010.00242
|View full text |Cite
|
Sign up to set email alerts
|

On the need for Embodied and Dis-Embodied Cognition

Abstract: This essay proposes and defends a pluralistic theory of conceptual embodiment. Our concepts are represented in at least two ways: (i) through sensorimotor simulations of our interactions with objects and events and (ii) through sensorimotor simulations of natural language processing. Linguistic representations are “dis-embodied” in the sense that they are dynamic and multimodal but, in contrast to other forms of embodied cognition, do not inherit semantic content from this embodiment. The capacity to store inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
156
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(169 citation statements)
references
References 137 publications
6
156
0
3
Order By: Relevance
“…Also, in keeping with the involvement of the motor system in processing action-related material, the results reported by Buccino et al [8] in a single pulse TMS study, have shown that motor evoked potentials (MEPs) recorded from hand muscles are modulated during listening to hand-related action sentences. Regarding abstract words, the issue is much more debated [9]. Scorolli et al [10] found M1 activation when TMS applied in an abstract verb condition was delayed (650 ms post-stimulus).…”
Section: Introductionmentioning
confidence: 99%
“…Also, in keeping with the involvement of the motor system in processing action-related material, the results reported by Buccino et al [8] in a single pulse TMS study, have shown that motor evoked potentials (MEPs) recorded from hand muscles are modulated during listening to hand-related action sentences. Regarding abstract words, the issue is much more debated [9]. Scorolli et al [10] found M1 activation when TMS applied in an abstract verb condition was delayed (650 ms post-stimulus).…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, I have raised questions about the strength of the evidence for neo-empiricist theories of concepts (Machery, 2006(Machery, , 2007; see also Dove, 2009Dove, , 2011Mahon & Caramazza, 2008), and I have questioned whether these theories can really explain how concepts "implement important conceptual functions," in particular how thought can express "propositions" (Machery, 2014). In this article, I will challenge the claim that there is little evidence for amodal theories of concepts, arguing that in fact a growing body of evidence shows that concepts are amodal.…”
Section: Introductionmentioning
confidence: 99%
“…Again, these models agree on a general division of labor in the acquisition of these two types of concepts, with concrete concepts being largely learned through sensorimotor experience, and abstract concepts being largely learned through linguistic experience (Andrews et al, 2009;Crutch & Warrington, 2005;Dove, 2009Dove, , 2011Louwerse & Jeuniaux, 2010;Steyvers, 2010). The behavioral data supporting this proposal, however, are still recent and limited.…”
Section: Introductionmentioning
confidence: 72%
“…Sensorimotor information . Free associationIn recent years, a diverse set of models regarding conceptual knowledge have proposed that multiple representational systems are engaged in conceptual processing (Andrews, Vigliocco, & Vinson, 2009;Barsalou, Santos, Simmons, & Wilson, 2008;Dove, 2009Dove, , 2011Louwerse & Jeuniaux, 2008Simmons, Hamann, Harenski, Hu, & Barsalou, 2008;Steyvers, 2010). In particular, they have all considered that both more sensorimotor-based information and languagebased information play a role in conceptual representation, thus recapturing the ideas first proposed by Paivio (1971Paivio ( , 1986 in the context of the dual-code theory.…”
mentioning
confidence: 88%
See 1 more Smart Citation